Improvement of Science Learning Outcomes Ruminant Animal Destruction System Materials Through Google Meet Media for Students Of Class V SD Negeri 2 Kedunggede - Sampurni, Nurdiyah (Universitas Sebelas Maret, 2020)
The purpose of this research was to improve the science learning outcomes of Ruminant Digestive System material through Google Meet media for fifth grade students of SD Negeri 2 Kedunggede. The research conducted was a Classroom Action Research (CAR) in three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is evaluated at the end of the lesson to find out the progress of students. In the first cycle, students who completed after conducting an evaluation at the end of the lesson were 61.5%. In the second cycle, students who completed after evaluating at the end of the lesson were 76.9%. In cycle III students who completed after conducting an evaluation at the end of the lesson were 80.8%. These results indicate that the use of Google Meet media can improve student learning outcomes, especially the science muple of the Ruminant Digestive System material for Grade V students at SDN 2 Kedunggede.